The reception history of 2 Thessalonians with special reference to John Chrysostom, Haimo of Auxerre, and John Calvin - Talbert, Andrew Rhett (2012)
Taking up the concept of reception history/Rezeptionsästhetik, as described by its founder, Hans Robert Jauss, this project considers the way in which diverse contexts shape the ways in which readers of 2 Thessalonians have historically interpreted the epistle. Supplementing Jauss’ methodology with insights from theological scholars, the larger questions of biblical meaning and continuity between biblical interpreters enters the discussion. In the former case, this research discounts the bifurcated directions of historical positivism that equates biblical meaning either with historical background or authorial intent. Related to this, the research proposes the continuity between historical interpreters of 2 Thessalonians be construed in terms of historical dialogue, which constitutes the being of the work. Three historical interpreters of 2 Thessalonians from different historical periods of the Church serve as the receptive foci in this dissertation: John Chrysostom (early Church), Haimo of Auxerre (Medieval Church), and John Calvin (Reformation). Following Jauss’ Rezpetionsästhetik, these interpreters are placed in their compositional contexts and in dialogue with modern interpreters of the same epistle. By passing through the various dimensions of the letter’s otherness, the research brings to the fore potential present appropriations of meaning.